Bat speed, trajectory, and timing for collegiate baseball batters hitting a stationary ball - Tabuchi, N.; Matsuo, T.; Hashizume, K. (Sports Biomechanics, 2007)
The aims of this study were to examine whether batters hit stationary balls at the time of peak speed of the bat head and whether the impact occurs at the lowest point of the bat trajectory. Eight university baseball players hit three balls, each hung with a string; each ball was made of a different material and was different in weight. Bat movement was captured by four 240-Hz infrared cameras and analysed three-dimensionally. Time for peak speed of the bat head varied according to the conditions. When stationary balls of standard weight were used, the bat head was at maximum speed at impact with the ball; then, it decelerated drastically owing to the impact. In contrast, maximum speed was obtained after impact when lightweight stationary balls were used. The time-speed profile of the bat head before impact in the lightweight ball condition was identical with that in the standard weight ball condition. Regardless of conditions, the timing of the lowest point of the bat head was nearly identical for each batter and most participants hit the stationary balls at about the lowest point of the bat trajectory.